ENT300 Kingdom Bookstore Trading / Nur Fateha Syuhaida... [et.al] - Mat Seman, Nur Fateha Syuhaida; Mohamad Anuar, Nur Najwa; Abu Hanafi, Noor Alysa; Arni, Nur Hazirah; Khairul Anuar, Noor Izni Hanun (2010)
The name of our company is Kingdom’s Bookstore. The business is in form of partnership which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is trading as we sell other people product at our bookstore. We also having a reading area for our customers to read the books. Our concept is also accurate and suitable with the campus way of life which the student’s time nowadays become more compact. Our business operation is at 10 am and 9 pm every day.